Deputy Daddy - Johns, Patricia (Romance writer) (Johns, Patricia (Romance writer) Comfort Creek lawmen., 2017)
Officer Bryce Camden never expected his two-week stint in Comfort Creek, Colorado, would mean diaper duty. But that's exactly what happens when he stays at the local bed-and-breakfast where Lily Ellison is fostering an abandoned baby girl. Bryce is drawn to the lovely B and B owner, but being a dad is not part of his plans. His troubled past has shown him that's not the nurturing type. But he soon finds himself wishing he didn't have to leave. Because Lily and the baby have taken root in his heart and made him think that maybe he could be a family man after all.